2016
DOI: 10.1016/j.marpolbul.2016.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon pollutants shape bacterial community assembly of harbor sediments

Abstract: Petroleum pollution results in co-contamination by different classes of molecules, entailing the occurrence of marine sediments difficult to remediate, as in the case of the Ancona harbor (Mediterranean Sea, Italy). Autochthonous bioaugmentation (ABA), by exploiting the indigenous microbes of the environment to be treated, could represent a successful bioremediation strategy. In this perspective we aimed to i) identify the main drivers of the bacterial communities' richness in the sediments, ii) establish enri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…As the original enrichment was generated from a dilbit spill, our data suggest that dilbit degradation may be faster in freshwater environments that have previously been exposed to crude oil hydrocarbons, as the environment may be selecting for bacterial communities capable of a rapid response [70]. These findings are also relevant to those interested in exploring the potential of autochthonous microbial consortia in bioaugmentation studies [71]. Sequencing analyses identified several bacteria that have previously been identified as hydrocarbon degraders, some of which have been detected in both freshwater and marine systems (e.g., Hydrogenophaga, Alcalinovorax, Novosphingobium, Pseudomonas, Dokdonella, Parvibaculum, Microbacterium).…”
Section: Discussionmentioning
confidence: 74%
“…As the original enrichment was generated from a dilbit spill, our data suggest that dilbit degradation may be faster in freshwater environments that have previously been exposed to crude oil hydrocarbons, as the environment may be selecting for bacterial communities capable of a rapid response [70]. These findings are also relevant to those interested in exploring the potential of autochthonous microbial consortia in bioaugmentation studies [71]. Sequencing analyses identified several bacteria that have previously been identified as hydrocarbon degraders, some of which have been detected in both freshwater and marine systems (e.g., Hydrogenophaga, Alcalinovorax, Novosphingobium, Pseudomonas, Dokdonella, Parvibaculum, Microbacterium).…”
Section: Discussionmentioning
confidence: 74%
“…This phylum is divided into five major classes, all with oil-degrading genera ( Gao et al, 2014 ). On the whole, isolated bacteria where ascribed mainly to genera belonging to Gamma-proteobacteria class, whose dominance within the enriched microcosms can be expected since it comprises many of the hydrocarbonoclastic bacteria responsible for the first steps of hydrocarbons degradation ( Head et al, 2006 ; Yakimov et al, 2007 ; Barbato et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In these works, the involvement of and Karlson, 2005;Simarro et al, 2013) Similar to the report by Simarro et al (2013) the heterotrophic bacteria counts were two orders of magnitude higher than contaminant-degrading bacteria. It has been reported that the soil microbial population changes with the addition of a contaminant (Yan et al, 2016) and that a specific microorganism selection takes place (Barbato et al, 2016). Furthermore, the ring structure are supported by Yang et al (2010), who indicated that sequestration is the major mechanism for the accumulation of PAHs in soils.…”
Section: Discussionmentioning
confidence: 96%